2013
DOI: 10.1155/2013/943256
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Mineralization of Organic Acids over Visible-Light-Driven Au/BiVO4Photocatalyst

Abstract: Au/BiVO 4 visible-light-driven photocatalysts were synthesized by coprecipitation method in the presence of sodium dodecyl benzene sulfonate (SDBS) as a dispersant. Physical characterization of the obtained materials was carried out by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), UV-Vis diffuse reflectance spectroscopy (DRS) and Brunauer, and Emmett and Teller (BET) specific surface area measurement. Photocatalytic performances of the asprepared Au/Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 35 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…RhB degradation follows a pseudo first-order reaction (Fig. 3(b)) as described by ln(C t /C 0 ) ¼ k app t where k app is the apparent rate constant (min À 1 ) and t is the reaction time [17]. The highest photocatalytic rate of 0.138 min À 1 (5 wt% f-GNPs), compared with 0.087 min À 1 (ZnO) and 0.002 min À 1 (non-catalysed reaction), is partly ascribed to the increased SSA of the nanocomposite (21.50 m 2 g À 1 ) compared with the pure ZnO (15.20 m 2 g À 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…RhB degradation follows a pseudo first-order reaction (Fig. 3(b)) as described by ln(C t /C 0 ) ¼ k app t where k app is the apparent rate constant (min À 1 ) and t is the reaction time [17]. The highest photocatalytic rate of 0.138 min À 1 (5 wt% f-GNPs), compared with 0.087 min À 1 (ZnO) and 0.002 min À 1 (non-catalysed reaction), is partly ascribed to the increased SSA of the nanocomposite (21.50 m 2 g À 1 ) compared with the pure ZnO (15.20 m 2 g À 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, high Ag loading accumulates a high surface density of negatively charged crystallites, where the positively charged photoholes will progressively be preferentially attracted by these particles, and thus will become electron-hole recombination centers inhibiting the reaction. degradation rate, C o /C is the ratio of the dyes at adsorptiondesorption equilibrium and after various intervals of time t and k is the apparent first-order rate constant (min −1 ) [37].…”
Section: Analysis Of Uv-visible Diffusive Reflectance Spectramentioning
confidence: 99%
“…Extensive research has currently been devoted to the development of visible-lightdriven catalysts with narrower bandgap energies. Since Kudo and coauthors firstly reported the photocatalysis of BiVO 4 (n-type, E g ≈ 2.4 eV) in 1998 [5], BiVO 4 has been one of the most frequently used materials for water purification and splitting due to its activity, chemical neutrality and stability, historical non-toxicity (e.g., the wide application as bright yellow pigment [6]), and environmental benign [7][8][9]. The n-type hematite (α-Fe 2 O 3 , E g ≈ 2.0 eV) is another superior photocatalyst of particular interest because of its low cost, environmental friendliness, easy preparation, and high thermodynamic stability [10][11][12].…”
Section: Introductionmentioning
confidence: 99%